Legal Regulation Experience of Individual Countries of The European Region Regarding Implementation of International Standards for Ensuring Criminological and Criminal-Legal Protection of Justice - Khrystova, Yuliia; Miroshnychenko, Serhiy; Kurbatova, Iryna; Titarenkо, Oleksiy; Maksimentsev, Maksym (Jurnal Cita Hukum, 2024)
The article describes the experience of Germany and Austria in implementing international standards for ensuring criminological and criminal-legal protection of justice. A set of general scientific and specific scientific research methods were used in the preparation of this article to define special subjects authorised to carry out such criminological activities, peculiarities of their interaction with the police and other law enforcement agencies, to reveal the content of legislative mandates regarding organisation and functioning of the Court Security Services and their counterparts, as well as that of the legislation on criminal liability for criminal offences against justice. The purpose of this work is to determine promising directions for increasing the efficiency of implementing criminological and criminal-legal protection of justice by authorised subjects in Ukraine, which has become especially important in the sphere of ensuring national security under martial law, taking into account positive experience of such European region countries as Germany and Austria regarding implementation of international standards recognised by the international community in this area. Based on the results of the research, prospective directions for improving the activity of the Court Security Service of Ukraine, its interaction with the National Police and other subjects of the state sector and non-state sector in the provision of criminological protection of justice, as well as the legislation of Ukraine on criminal liability for criminal offences against justice, taking into account experience of Germany and Austria regarding implementation of standards recognised by the international community in this area.